Host specificity and zoonotic Enterocytozoon bieneusi genotypes in wild rodents from the Inner Mongolian Autonomous Region and Liaoning Province of China - Zhao, Wei; Sun, Lijie; Liu, Li; Jiang, Aiying; Xiao, Qiang; Tan, Feng (Frontiers in Cellular and Infection Microbiology, 2024)
Wild rodents can serve as reservoirs or carriers of E. bieneusi, thereby enabling parasite transmission to domestic animals and humans. This study aimed to investigate the prevalence of E. bieneusi in wild rodents from the Inner Mongolian Autonomous Region and Liaoning Province of China. Moreover, to evaluate the potential for zoonotic transmission at the genotype level, a genetic analysis of the isolates was performed. A total of 486 wild rodents were captured from two provinces in China. Polymerase chain reaction (PCR) was performed to amplify the vertebrate cytochrome b (cytb) gene in the fecal DNA of the rodents to detect their species. The genotype of E. bieneusi was determined via PCR amplification of the internal transcribed spacer (ITS) region of rDNA. The examination of genetic characteristics and zoonotic potential requires the application of similarity and phylogenetic analysis. The infection rates of E. bieneusi in the four identified rodent species were 5.2% for Apodemus agrarius (n = 89), 4.5% for Cricetulus barabensis (n = 96), 11.3% for Mus musculus (n = 106), and 38.5% for Rattus norvegicus (n = 195). Infection was detected at an average rate of 17.4% among 486 rodents. Of the 11 identified genotypes, nine were known: SHR1 (detected in 32 samples), D (30 samples), EbpA (9 samples), PigEbITS7 (8 samples), HNR-IV (6 samples), Type IV (5 samples), HNR-VII (2 samples), HNH7 (1 sample), and HNPL-V (1 sample). Two novel genotypes were also discovered, NMR-I and NMR-II, each comprising one sample. The genotypes were classified into group 1 and group 13 via phylogenetic analysis. Based on the initial report, E. bieneusi is highly prevalent and genetically diverse in wild rodents residing in the respective province and region. This indicates that these animals are crucial for the dissemination of E. bieneusi. Zoonotic E. bieneusi-carrying animals present a significant hazard to local inhabitants. Therefore, it is necessary to increase awareness regarding the dangers presented by these rodents and reduce their population to prevent environmental contamination.